Pengaruh Budaya Organisasi dan Motivasi Pegawai terhadap Komitmen Organisasi Pegawai Badan Pusat Statistik (BPS) Kota Jambi - Candra Irawan; Dahmiri Dahmiri; Ovie Yanti (MASMAN Master Manajemen, 2026)
Employee organizational commitment at the Central Bureau of Statistics (BPS) of Jambi City refers to the level of psychological attachment, loyalty, and willingness of employees to remain part of the organization and contribute optimally to achieving institutional goals. This commitment reflects the extent to which employees possess a sense of belonging, accept organizational values, and demonstrate seriousness in carrying out their duties and responsibilities as public servants. This study aims to determine and analyze the influence of organizational culture and employee motivation on employee organizational commitment at the Central Bureau of Statistics of Jambi City. The research method used is a descriptive quantitative approach with data collection techniques through observation and questionnaire distribution to respondents. The data analysis method used is multiple linear regression analysis with the assistance of SPSS version 25 software. The results of the study indicate that, based on the t-test, organizational culture and employee motivation partially have a positive and significant effect on employee organizational commitment at the Central Bureau of Statistics of Jambi City. In addition, based on the F-test, organizational culture and employee motivation simultaneously have a significant effect on employee organizational commitment at the Central Bureau of Statistics of Jambi City.